IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS FOR SMALL AND MEDIUM MICRO-ENTITIES IN THE PREPARATION OF FINANCIAL STATEMENTS - Darul Fahmi (Jurnal Scientia, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are business activities that can expand employment opportunities and provide broad economic services to the community and can play a role in equalizing and increasing community income, encouraging economic growth, and participating in national development. Financial statements aim to analyze financial performance as a benchmark for providing information about a company's financial position and profit and loss, which is helpful for users of financial statements as economic decision-makers. This research is intended for MSME owners who still need financial reports. This research aims to help and facilitate MSME owners in compiling financial reports based on SAK EMKM. This research is a research using descriptive qualitative method. Data collection was carried out using observation, interviews, and documentation. Thus, this study shows that in carrying out its operational activities.